The cork viewed from the inside - Lagorce-Tachon, Aurélie; Karbowiak, Thomas; Loupiac, Camille; Gaudry, Alexandre; Ott, Frédéric; Alba-Simionesco, Christiane; Gougeon, Régis D.; Alcantara, Valentin; Mannes, David; Kaestner, Anders; Lehmann, Eberhard; Bellat, Jean-Pierre (Journal of Food Engineering, 2015)
Cork is the natural material stripped from the outer bark of cork oak. It is still the most used stopper to seal wine bottles and to preserve wine during storage. Cork stoppers are sorted in different classes according to apparent defects, named lenticels, which can be related to the cork macroporosity. The more lenticels there are, the worst cork quality is. The present work aims at investigating defects analysis of cork stoppers from two classes by comparing digital photography and neutron imaging. Surface analysis of defects obtained from photography leads to more surface defects in class 4 (6.7%) than in class 0 (4.1%). Neutron radiography and tomography are powerful methods that really show the defects inside the material. From neutron radiography and tomography, class 0 contains 5.4% of volume defects and class 4 6.5%. Moreover, tomography also allows observing defects distribution along the whole stopper and possible interconnectivity.
Keywords: Cork; defect detection; image analysis; neutron imaging; Porosity; tomography